Framing as a mechanism to overcome the temptation of bad habits - Wang, Shuning; Monterosso, John (Frontiers in Behavioral Neuroscience, 2025)
Behavioral neuroscience generally conceives of habits as under stimulus-response control, and distinguishes habits from goal-directed behavior based on their insensitivity to outcome value (features of automaticity). However, the everyday meaning of “bad habits” is applied primarily to behaviors that are compelling, in part, because of their anticipated outcome value. In particular, commonly identified bad habits (e.g., overuse of social media, overeating, smoking) are repeated behaviors that yield appealing immediate outcomes, but at a greater longer term cost (“temptations”). We begin by evaluating the role of both automaticity and temptation in the maintenance of bad habits. Next we focus on how framing effects can be used to shift the balance of motivation away from immediate and/or toward delayed outcome value, including a partial summary of what is known about the neural substrates that mediate such shifts. We pay particular attention to the way frames can promote replacing bad habits with good habits through emphasizing the connection between specific choices and general policy preferences.